Foreign exchange in the postwar world - Mikesell, Raymond Frech (New York : Twentieth Century Fund, 1954)
This book examines the issues of world's currency problems, and brings together in one volume information on the exchange control systems and international payments arrangements of the countries of the world.
Includes index
Bibliographical footnotes.
usc 08/05/18; 08/06/18
Loans
Keywords: Foreign exchange; Payments mechanism